UV Irradiation Exposure of Polymer Composite Filled with Recycled Unused Diapers - Kho, Dick; Mohd Rus, Anika Zafiah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The research aimed to address the issue of waste diaper pollution through the fabrication and analysis of polymer composites containing recycled unused diapers (RD) combined with Polypropylene (PP) and Polyethylene (PE) at various ratios. The objectives were to determine the mechanical properties of the composites before and after UV irradiation and thermal exposure. To achieve these objectives, waste diapers were mixed with Polypropylene and Polyethylene at ratios of 〖PD〗_5, 〖PD〗_10, 〖PD〗_(15 ), 〖PD〗_(20 )and 〖PD〗_25 and 〖PED〗_5, 〖PED〗_10, 〖PED〗_15, 〖PED〗_20, and 〖PED〗_25, respectively. Tensile testing and Shore D hardness testing were conducted on the specimens before and after UV irradiation to evaluate their mechanical properties. The specimens were also subjected to UV irradiation at predetermined temperature and time. Optical microscope analysis was performed to observe surface fractures after UV irradiation. The results revealed that the composite with a composition ratio of 〖PD〗_(10 )exhibited the highest average stress of 45.4128〖N/mm〗^2 at the 4-hour mark after UV irradiation exposure at 50°C. Additionally, the composite with a composition ratio of 〖PD〗_5 demonstrated the highest average strain of 17.2038 at the 1-hour mark after UV irradiation exposure at 50°C. Similar trends were observed at different temperatures and exposure times. For the Polyethylene composites, the composition ratio 〖PED〗_25 showed the highest average stress of 17.961〖N/mm〗^2 at the 4-hour mark after UV irradiation exposure at 50°C. The composition ratio 〖PED〗_10 exhibited the highest average strain of 22.1316 at the 4-hour mark after UV irradiation exposure at 50°C. Comparable findings were observed for different temperature and exposure time conditions. In conclusion, the research successfully fabricated polymer composites incorporating recycled unused diapers and evaluated their mechanical properties before and after UV irradiation exposure. The results indicate that specific composition ratios exhibited superior stress and strain values under different UV irradiation conditions. These findings contribute to understanding the potential of utilizing waste diapers in composite materials, which can aid in addressing waste diaper pollution and promoting sustainable waste management practices.